Democratization and political transition in Arab World: Prospects and challenges - Mikail, Ibrahim Kawuley; Abdullah, Mohamad Ainuddin Iskandar Lee (Universiti Tun Hussein Onn Malaysia, 2015)
Democracy and Democratization process was among the top priorities in the new post-cold war global agenda.This issue has convinced some undemocratic countries of Arab World to set up in quest for democracy and to assertively demand their long-denied socio-economic and political justice by the autocratic rulers for the region.Indeed, the current Arab spring is geared towards transition from undemocratic system (i.e. Monarchy and Military dictatorship) to democracy.Secondary data was adopted in this study.The study revealed that humiliation, prolong monarchy/military dictatorship, lack of economic reform, globalization and proliferation of mass literacy were among the factors responsible for political transition in the region.Meanwhile, establishment of tenets of democracy (i.e. rules of law, human rights, freedom, etc.) and insecurity, external domination and loss of lives were among the prospect and challenges of the transition.The paper recommended among others that there is need for political and economic reform in the Arab countries which would lead to transit to democracy.